Varus-valgus constrained implants in total knee arthroplasty: indications and technique - Adravanti, Paolo; Vasta, Sebastiano (Acta Biomedica Atenei Parmensis, 2017)
Total knee arthroplasty is a successful operation that significantly improves patient’s quality of life. However, studies demonstrated as only 82% to 89% of patients are satisfied with their surgery, being the other disappointed with regard to their expectations. Two to 5.7% of total knee arthroplasties (TKAs) require revision within 5 years. Both complex primary cases and revision TKA often necessitate for a higher degree of constrain than cruciate retaining or postero-stabilized implant design. In the 1970s varus-valgus constrained (VVC) or semi-constrained implants have been developed by Insall and associates from the PS design, which provide varus-valgus stability preserving a fair amount of host bone. VVC TKAs allows for a small amount of movement in the coronal, antero-posterior and axial planes. In this paper, the authors give an overview of the indications, outcomes and technique for varus-valgus constrained implants, both in the setting of primary and revision knee arthroplasty.